Monitoring Lakes Water Based on Multisource Remote Sensing and Novel Modeling Techniques - Zhang, Fei; Chan, Ngai Weng; LI, Xinguo; Wang, Xiaoping (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Inland lakes are indicators of climate change and environmental deterioration. As a unique ecosystem unit, an inland lake is one of the basic locations for human survival and development. In recent years, with the rapid development of regional society and economy, the ecological environment of inland lakes has been continuously disturbed by human activities under the influence of large-scale water and soil exploitation activities, which have affected the ecological environment of lakes. Therefore, lake ecological restoration and water quality monitoring under the coupled effect of climate change and human activities are the key to lake protection and management. In recent years, remote sensing has played an increasingly important role in the monitoring of the terrestrial water cycle. Remote sensing technology has been applied in many fields, such as water storage, water quality, water level, and hydrodynamics. Furthermore, the explosive growth of remote sensing data applications is driven by the coupling of multisource remote sensing data and the expansion of new modeling technology.